Designing and implementing a kindergarten‐based, family‐involved intervention to prevent obesity in early childhood: the ToyBox‐study. (August 2014) - Manios, Y.; Androutsos, O.; Katsarou, C.; Iotova, V.; Socha, P.; Geyer, C.; Moreno, L.; Koletzko, B.; De Bourdeaudhuij, I.; ,
Summary: The development of the ToyBox‐intervention was based on the outcomes of the preliminary phase of the ToyBox‐study, aiming to identify young children's key behaviours and their determinants related to early childhood obesity. The ToyBox‐intervention is a multi‐component, kindergarten‐based, family‐involved intervention with a cluster‐randomized design, focusing on the promotion of water consumption, healthy snacking, physical activity and the reduction/ breaking up of sedentary time in preschool children and their families. The intervention was implemented during the academic year 2012–2013 in six European countries: Belgium, Bulgaria, Germany, Greece, Poland and Spain. Standardized protocols, methods, tools and material were used in all countries for the implementation of the intervention, as well as for the process, impact, outcome evaluation and the assessment of its cost‐effectiveness. A total sample of 7, 056 preschool children and their parents/caregivers, stratified by socioeconomic level, provided data during baseline measurements and participated in the intervention. The results of the ToyBox‐study are expected to provide a better insight on behaviours associated with early childhood obesity and their determinants and identify effective strategies for its prevention. The aim of the current paper is to describe the design of the ToyBox‐intervention and present the characteristics of the study sample as assessed at baseline, prior to the implementation of the intervention.